PENGARUH RETURN ON EQUITY, EARNING PER SHARE, FIRM SIZE DAN OPERATING CASH FLOW TERHADAP RETURN SAHAM - Aisah, Ayu Nurhayani; Mandala, Kastawan (E-Jurnal Manajemen, 2016)
This study aims to determine the effect of return on equity, earnings per share, firm size and operating cash flow to stock return. This study was performed on companies listed in the Index Kompas 100 2011-2015. The sampling technique that used in this research is purposive sampling technique. This study has 22 companies samples. Data analysis technique that used is multiple linear regression analysis. Based on the results of the research analysis found operating cash flow has a positive and significant effect on stock returns , EPS has a negative and significant effect on stock returns where as ROE and firm size has no effect on stock returns.
Keywords: return on equity, earning per share, firm size, operating cash flow, stock return